Case report of the first successful cryopreserved ovarian tissue retransplantation in China. (2nd November 2018) - Ruan, X.; Du, J.; Korell, M.; Kong, W.; Lu, D.; Jin, F.; Li, Y.; Dai, Y.; Yin, C.; Yan, S.; Gu, M.; Mueck, A. O.
Abstract: Ovarian tissue cryopreservation and retransplantation has been offered as a fertility preservation approach for over a decade. At least 130 live births have been reported after frozen–thawed ovarian tissue transplantation worldwide. The first International Fertility Protection Center in China was established in 2015. Until now no live birth has been reported. However, we are able to report the first Chinese successful retransplantation of cryopreserved ovarian tissue (September 2016) in a woman with squamous cell cervical carcinoma. Restoration of ovarian endocrine function was shown in the third month after transplantation, and after 21 months of follow-up the transplants are still active and maintaining good function. This first report of successful retransplantation represents a milestone in the field of fertility preservation in China.